2011
DOI: 10.5324/nje.v20i1.1297
|View full text |Cite
|
Sign up to set email alerts
|

Health-related benefits among children in the child welfare system: prevalence and determinants of basic and/or attendance benefits

Abstract: Objective: To examine the prevalence and determinants of basic and/or attendance benefits among children involved with the child welfare system (CWS). Design: A register study of all children involved with CWS in Norway from [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006]. Participants: 96,354 children from the CWS group and 149,030 children who had never been in the CWS as a comparison group. Results: 11% of children involved with CWS received basic and/or attendance benefits compared to 3% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…In Sweden, approximately 4% of all children are at some time during their childhood placed in societal out‐of‐home care (OHC, foster family or residential care), around the same proportion as in Denmark and the UK (Fallesen, Emanuel, & Wildeman, ; McGrath‐Lone, Dearden, Nasim, Harron, & Gilbert, ; Vinnerljung, ; Vinnerljung, Hjern, Weitoft, Franzén, & Estrada, ). For several decades, studies from various Western countries have reported strikingly high levels of somatic health problems in this group of children (Arora, Kaltner, & Williams, ; Chernoff, Combs‐Orme, Risley‐Curtiss, & Heisler, ; Halfon, Mendonca, & Berkowitz, ; Hansen, Mawjee, Barton, Metcalf, & Joye, ; Kling, Vinnerljung, & Hjern, ; Nathanson & Tzioumi, ; Schor, ; Steele & Buchi, ; Turney & Wildeman, ; Zewdu, ). In addition, adults with childhood experience of OHC have far higher rates of health problems than peers without this background (Vinnerljung, Brännström, & Hjern, ; Schneider et al, ; Viner & Taylor, ; Zlotnick, Tam, & Soman, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, approximately 4% of all children are at some time during their childhood placed in societal out‐of‐home care (OHC, foster family or residential care), around the same proportion as in Denmark and the UK (Fallesen, Emanuel, & Wildeman, ; McGrath‐Lone, Dearden, Nasim, Harron, & Gilbert, ; Vinnerljung, ; Vinnerljung, Hjern, Weitoft, Franzén, & Estrada, ). For several decades, studies from various Western countries have reported strikingly high levels of somatic health problems in this group of children (Arora, Kaltner, & Williams, ; Chernoff, Combs‐Orme, Risley‐Curtiss, & Heisler, ; Halfon, Mendonca, & Berkowitz, ; Hansen, Mawjee, Barton, Metcalf, & Joye, ; Kling, Vinnerljung, & Hjern, ; Nathanson & Tzioumi, ; Schor, ; Steele & Buchi, ; Turney & Wildeman, ; Zewdu, ). In addition, adults with childhood experience of OHC have far higher rates of health problems than peers without this background (Vinnerljung, Brännström, & Hjern, ; Schneider et al, ; Viner & Taylor, ; Zlotnick, Tam, & Soman, ).…”
Section: Introductionmentioning
confidence: 99%
“…I sin studie om norske barn i barnevernet som får grunn-og hjelpestønad viser Zewdu (2010) til flere studier som finner at barn i barnevernet har større sannsynlighet for å ha fysiske og psykiske helseproblemer, og studier fra USA viser at majoriteten av barn som er i fosterhjem har minst en kronisk tilstand (50-80 %). De kroniske tilstandene det hyppigst rapporteres om er; fedme, astma, bronkitt, syn-og hørselsproblemer, feilernaering, fysiske skader, følelsesmessige problemer, og atferd og tilpasningsproblemer (Zewdu 2010). Danske studier viser at andelen barn som mottar hjelpetiltak eller er under barnevernets omsorg, oftere har diagnoser knyttet til atferd som ADHD, enn i den øvrige barnebefolkningen (Ottosen og Christensen 2008).…”
Section: Forekomstunclassified
“…I dag eksisterer det et stort kunnskapshull når det gjelder spørsmålet om hvor mange barn og unge med funksjonsnedsettelser som får hjelpe-eller omsorgstiltak fra barnevernet. Som vist i kapittel 2.1 så finner internasjonale studier at det er relativt mange barn og unge med en funksjonsnedsettelse i barnevernet, hvorvidt dette også er tilfelle i Norge vet vi ikke, men vi har indikasjoner på at dette også kan vaere tilfelle her (Zewdu 2010). Slik vi ser det er denne typen kunnskap relevant av flere grunner.…”
Section: Videre Forskningunclassified